HPV16/18 prevalence in high-grade cervical lesions in an Australian population offered catch-up HPV vaccination. Issue 40 (11th September 2020) - Cornall, Alyssa M.; Saville, Marion; Pyman, Jan; Callegari, Emma T.; Tan, Fiona H.; Brotherton, Julia M.L.; Malloy, Michael J.; Tabrizi, Sepehr N.; Wrede, C. David; Garland, Suzanne M.; ,
Abstract: Objectives: Using laser capture microdissection (LCM) and sensitive human papillomavirus (HPV) genotyping, we aimed to determine the distribution of vaccine-preventable types in cervical intraepithelial neoplasia grade 3 (CIN3) lesions and adenocarcinoma in situ (AIS) in young women in Victoria, Australia, offered catch-up HPV vaccination, as a baseline for ongoing vaccine impact monitoring. We also compared findings with available pre-vaccination estimates from women with HPV detected on concurrently-collected cytology samples. Methods: Consecutive histologically-confirmed CIN3/AIS biopsies were collected between May 2011 and December 2014 from vaccine-eligible women (born after 30th June 1981). Genotypes present in whole tissue sections (WTS) were determined by a sensitive reverse hybridisation assay; RHA kit HPV SPF10-LiPA25, v1 (Labo Bio-medical Products). Where multiple genotypes were detected, lesions were isolated using LCM and genotyped. Cervical cytology samples from a pre-vaccine cohort had been previously collected and genotyped using HPV Linear Array HPV Genotyping Test (Roche Diagnostics). Mixed-genotype detections in this cohort were resolved to single-lesion-attributable genotypes using hierarchical attribution. Results: Overall, 213 and 530 cases were included from pre- and post-vaccine time-periods, respectively. In 18–25 year-olds, the proportion of HPV16/18-positive CIN3/AIS decreased significantly over time from 69% in 2001–2005 (pre-vaccine), to 62% in 2011–2012 (post-vaccine), to 47% in 2013–2014 (p-trend = 0.004). There was no significant change in HPV16/18 in 26–32 year-olds (p-trend = 0.15). In 2013/14, nonavalent vaccine types accounted for 80% of CIN3/AIS in 18–25 year old women and 90% in 26–32 year old women. Conclusion: Four to 8 years following implementation of HPV vaccination in Australia, approximately 70% of CIN3/AIS in young women was due to HPV16/18. Our data, despite some limitations due to change in methods between pre- and post-vaccine periods, suggests that for vaccine-eligible women aged 18–25 at the time of biopsy, the proportion of HPV16/18-attributable CIN3/AIS lesions is significantly declining post-vaccination.